1998
DOI: 10.1046/j.1523-1755.1998.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of long bones in renal failure: Roles of hyperparathyroidism, growth hormone and calcitriol

Abstract: Calcitriol counteracts the trophic actions of growth hormone on epiphyseal growth plate cartilage and modifies chondrocyte differentiation in vivo, and these mechanisms may contribute to disturbances in longitudinal bone growth in renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 22 publications
13
108
2
1
Order By: Relevance
“…The animals had free access to drinking water and standard rodent diet containing 23.4% protein, 0.6% calcium, and 0.6% phosphorus (Purina Mills, Indianapolis, IN). After 24 h of acclimatization, 37 rats underwent the first stage of a two-stage 5/6 nephrectomy (Nx) under ketamine and xylazine anesthesia (11). The second stage nephrectomy was completed 7 d later, and seven animals underwent thyroparathyroidectomy (TPTX) at the same time (12).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The animals had free access to drinking water and standard rodent diet containing 23.4% protein, 0.6% calcium, and 0.6% phosphorus (Purina Mills, Indianapolis, IN). After 24 h of acclimatization, 37 rats underwent the first stage of a two-stage 5/6 nephrectomy (Nx) under ketamine and xylazine anesthesia (11). The second stage nephrectomy was completed 7 d later, and seven animals underwent thyroparathyroidectomy (TPTX) at the same time (12).…”
Section: Methodsmentioning
confidence: 99%
“…A group of ten nephrectomized animals received calcitriol (Nx-D) at a daily dose of 50 ng/kg per d by intraperitoneal injection 10 d before sacrifice. The dose and duration of calcitriol therapy was based on an earlier study that showed changes in the growth plate only after 10 d of treatment (11).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations